Ecological conditions of growth and breeding analysis of Viburnum opulus L. populations in the Kazakhstan part of the Altai Mountains - ALEVTINA N. DANILOVA; TATIANA A. VDOVINA; ELENA A. ISAKOVA; YURI A. KOTUKHOV; AIDAR A. SUMBEMBAYEV (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Danilova AN, Vdovina TA, Isakova EA, Kotukhov YA, Sumbembayev AA. 2024. Ecological conditions of growth and breeding analysis of Viburnum opulus L. populations in the Kazakhstan part of the Altai Mountains. Biodiversitas 25: 2845-2857. The purpose of this paper was to study the ecological growth conditions of Viburnum opulus populations and the variability of the main morphological parameters of the vegetative and generative spheres of the species at the interpopulation level in the Kazakhstan part of the Altai Mountains as a future promising donor for breeding work. As a result of field research, using route-reconnaissance, traditional geobotanical, and morphometric methods, 24 isolated locations of V. opulus were discovered in the Kazakhstan Altai in the geographical areas of Kalbinsky, Western, and Southern Altai. These areas' ecological conditions of the species growth were studied for the first time, based on which the characteristics of plant communities with the participation of V. opulus were compiled. It was found that the species grows mainly in three types of associations: tree-shrub, shrub-meadow in the forest zone, and steppe shrub-meadow in the mountain-steppe zone. Plant communities with the participation of V. opulus occupy areas on the northwestern and southeastern mountain slopes associated with river valleys. The vertical range of distribution of the species varies from 395 to 913 masl. The total area of the territory occupied by plant communities with the participation of V. opulus was 198.85 ha. Furthermore, when studying interpopulation variability in 9 populations isolated from each other and located in different ecological and geographical growing conditions, 3 main groups of characteristics were identified depending on the degree of variability. High variability was revealed in the height of the shrubs, fruits in the cluster and their weight, the color of ripe berries, taste indicators for fruit bitterness from 1 to 4 points, and yield. Promising populations regarding productivity were identified in Kalbinsky, Western, and Southern Altai, depending on the ecological and geographical growth in the Kazakhstan Altai.